Superior thyroid artery mean peak systolic velocity for the diagnosis of thyrotoxicosis in Japanese patients - Hirose, Takahisa; Takahashi, Satomi; Uchida, Toyoyoshi; Sakai, Ken; Goto, Masahiro; Kubo, Sayaka; Takeno, Kageumi; Kanno, Rei; Azuma, Kousuke; Kawamori, Ryuzo; Fujitani, Yoshio; Watada, Hirotaka (ENDOCRINE JOURNAL, 2010)
Thyrotoxicosis with diffuse thyroid disease can be caused by Graves’ disease (GD) or destructive thyroiditis (DT). Optimal treatment of the underlying condition requires a prompt and accurate method for the diagnosis of thyrotoxicosis. This study evaluated measurement of the mean peak systolic velocity of the superior thyroid artery (STA-PSV) by ultrasonography in detecting thyrotoxicosis in Japanese patients. We recruited 44 patients with untreated GD, 13 with DT, 55 with treated GD, and 49 subjects without thyroid disease. Blood samples were taken to analyze thyroid function and STA-PSV was measured by ultrasonography. The mean STA-PSV was the highest in the untreated GD group, followed by treated GD patients and then those with DT. Receiver operating characteristic curves of the STA-PSV values demonstrated that the area under the curve required discriminating untreated GD from DT was 0.941. The optimal sensitivity and specificity were 83.7% and 92.3%, respectively, using 45 cm/sec as the cutoff value. In conclusion measurement of STA-PSV by ultrasonography is useful for the diagnosis of thyrotoxicosis in Japanese patients.